Yayasan UMP contributes to flood victims - Mimi Rabita, Abd Wahit (2021)
JERANTUT, 11 January 2021 - A total of 100 flood victims in Jerantut received food kit assistance and necessities as well as personal hygiene kit from Yayasan UMP and the Student Volunteer Foundation (YSS) in the Ziarah UMP-KPT Prihatin Programme to help those still staying at the temporary relief centres (PPS) around Jerantut.